A Study on Jaco-Type Graphs - Kok, Johan; Sudev, N. K.; Chithra, K. P. (Journal of Informatics and Mathematical Sciences, 2016)
For a sequence \({a_n}\) in general such that \(a_n N\) and \(a_n+1a_n\), \(n=1,2,3,…\), a new population of directed graphs is defined such that for a given sequence \({a_n}\) the infinite directed root-graph has \(d^+(v_n)=a_n\). The infinite directed root-graph is denoted \(J_∞({a_n})\). The family of finite Jaco-Type graphs is the set of directed graphs \(J_n({a_n})\), \(nN\) by lobbing off all vertices and arcs in \(J_∞({a_n})\) for vertices \(v_i\), \(i > n\). We present introductory results for two families of these new directed graphs.